Characterization of Continuous-Wave Laser Crystallized Silicon Thin Films with Hole-Patterns. (1st May 2022) - Nguyen, Thi Thuy; Kuroki, Shin-Ichiro
Abstract : Single crystal grain low-temperature polycrystalline thin-film transistors (LTPS-TFTs) fabricated on a glass substrate have been the key target to develop transparent electronics such as monolithic three-dimensional integrated circuits (3DICs) and glass sheet computers because of their ultrahigh-performances. This study proposed a simple method to pre-define single-crystal grains with hole-patterned polycrystalline silicon (poly-Si) thin film. The crystal growth and the temperature distribution were clarified by observing the characterization of a hole-patterned poly-Si thin film. The relationship between the temperature gradient, crystal growth, and void formation in the poly-Si thin film was discussed. The location of voids was controllable in the hole-patterned poly-Si thin film. These pre-defined single-crystal grains are promising to fabricate ultrahigh-performance LTPS-TFTs.